A community-based group exercise program for persons with chronic stroke. - Eng JJ; Chu KS; Kim CM; Dawson AS; Carswell A; Hepburn KE (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The purpose of this study was to evaluate the physical and psychosocial effects of an 8-wk community-based functional exercise program in a group of individuals with chronic stroke. METHODS: Twenty-five subjects (mean age 63 yr) participated in a repeated measures design that evaluated the subjects with two baseline assessments 1 month apart, one postintervention assessment, and one retention assessment 1 month postintervention. Physical outcome measures assessed were the Berg Balance Test, 12-Minute Walk Test distance, gait speed, and stair climbing speed. Psychosocial measures assessed were the Reintegration to Normal Living Index (RNL) and Canadian Occupational Performance Measure (COPM). The 8-wk training consisted of a 60-min, 3 x wk-1 group program that focused on balance, mobility, functional strength, and functional capacity. The program was designed to be accessible by reducing the need for costly one-on-one supervision, specialized settings, and expensive equipment. RESULTS: Improvements from the exercise program were found for all physical measures and these effects were retained 1-month postintervention. Subjects with lower function improved the most relative to their initial physical status. Significant effects were found for the COPM, but not the RNL Index; however, subjects with lower RNL improved the most relative to their initial RNL Score. CONCLUSION: A short-term community-based exercise program can improve and retain mobility, functional capacity, and balance and result in a demonstrable impact upon the performance of activities and abilities that were considered meaningful to the subjects. Implementation of such community-based programs has potential for improving activity tolerance and reducing the risk for secondary complications common to stroke (e.g., falls resulting in fractures and cardiac events).